TYM TEST – novel diagnostic tool to assess cognitive functions – study on inhabitants of social welfare house - Derkacz, Marek; Chmiel-Perzyńska, Iwona; Kowal, Agnieszka; Pawlos, Joanna; Michałojć-Derkacz, Magdalena; Olajossy, Marcin; Marczewski, Krzysztof (Current Problems of Psychiatry, 2011)
Cognitive impairment can affect the daily functioning of older people and worsen their quality of life. The aim of this study was to assess cognitive functions using TYM-test, a new diagnostic tool and to compare obtained test results with the results in MMSE test. The survey was conducted among 65 residents of the Social Welfare Home (SWH) in Lublin. The average age of the study group was 76.2 years ± 12.2. We found the strong correlation between the results obtained in TYM-test and MMSE scale – in the final scoring (p